Both high expression of pyruvate kinase M2 and vascular endothelial growth factor-C predicts poorer prognosis in human breast cancer - Lin, Yang (Int J Clin Exp Pathol, 2015)
Pyruvate kinase M2 (PKM2) and vascular endothelial growth factor-C (VEGF-C) have been known to play an important role in tumorigenesis and tumor progression in breast cancer. However, the association between PKM2 and VEGF-C in breast cancer remains unclear. In the present study, a total of 218 specimens from breast cancer patients and 26 paired breast tumors with adjacent normal tissues as well as two breast cancer cell lines were enrolled to investigate the correlation between PKM2 and VEGF-C. We found that PKM2 and VEGF-C mRNA levels were both significantly increasing in breast tumors compared with adjacent normal tissues. Knockdown of PKM2 mRNA expression resulted in VEGF-C mRNA and protein down-regulated as well as cell proliferation inhibited. A positive correlation between PKM2 and VEGF-C expression was identified by immunohistochemical analyses of 218 specimens of patients with breast cancer (P=0.023). PKM2 high expression was significantly correlated with histological grade (P=0.030), lymph node stage (P=0.001), besides VEGF-C high expression was significantly associated with lymphovascular invasion (P=0.012). While combined high expression of PKM2 and VEGF-C was found to be associated with worse histological grade, more lymph node metastasis, more lymphovascular invasion, shorter progression free survival (PFS), and poorer overall survival (OS) in human breast cancer. The results of the present study suggested that PKM2 expression was correlated with VEGF-C expression, and combination of PKM2 and VEGF-C levels had the better prognostic significance in predicting the poor outcome of patients with breast cancer.